AWARENESS AND ISSUES IN THE ADOPTION AND IMPLEMENTATION OF TRANSFER PRICING: A PERCEPTIONAL STUDY AMONG THE VARIOUS KINDS OF BUSINESS - Kumar, Sathya; Ponniah, V.M. (International Journal of Psychosocial Rehabilitation, 2020)
Transfer pricing influences the tax base of the countries involved in cross-border transactions. In any cross border tax scenario, the parties involved are the relevant entities of the MNE group along with the tax authorities. Transfer Pricing authorities while dealing with assesses there is negative response and hence, these issues need thorough investigation and necessary modification in the structural aspects of the provisions of the act. In this scenario, the present study is taken up to find out the awareness and general and specific issues affecting the adoption and implementation of transfer pricing among the business firms in Chennai city. A descriptive methodology with the sample size of 442 is conducted. The data required is collected through a structured and tested questionnaire. The results show that, each dimension of issue is faced by the set of firms in the sample, namely awareness, modus operandi, internal and external issues. Creating awareness, resolving policy issues by the government, internal issues by the management and audit related issues in consultation with the experts can help in improving the adoption and implementation of transfer pricing tax system among the firms in a phased manner.